1997
DOI: 10.7901/2169-3358-1997-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Prediction for Barge Buffalo 292 Spill

Abstract: The oil spill trajectory prediction for the barge Buffalo 292 spill was provided by NOAA and TGLO. The bulk of the 5000 barrels of IFO 380 that was leaked moved rapidly through the Galveston Channel entrance and into the Gulf of Mexico as a result of a strong meteorological event. Because of the nature of the product, it was possible to track the resulting slicks for more than 3 weeks. Initially, the oil trailed east away from shore. Changing winds and currents moved the oil south and west, leading to sporadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The cause of this buoy sinking in the first place (an inadequate mooring design) has since been redesigned to allow the buoys to survive 30-foot seas and 100-knot winds. (Lehr et al, 1997;Martin et al, 1997;Guinasso et al, 2001). Working closely together, TGLO's and NOAA's trajectory modelers determined that the downcoast flow would hold for many more days taking the oil to the southwest and away from Sabine Pass.…”
Section: Lessons Learned and Modifications Madementioning
confidence: 99%
See 1 more Smart Citation
“…The cause of this buoy sinking in the first place (an inadequate mooring design) has since been redesigned to allow the buoys to survive 30-foot seas and 100-knot winds. (Lehr et al, 1997;Martin et al, 1997;Guinasso et al, 2001). Working closely together, TGLO's and NOAA's trajectory modelers determined that the downcoast flow would hold for many more days taking the oil to the southwest and away from Sabine Pass.…”
Section: Lessons Learned and Modifications Madementioning
confidence: 99%
“…On 16 February 1995, an impact was reported along 18 miles of beach on Matagorda Island. Fingerprinted samples revealed that the impact to Matagorda Island was very likely the same product spilled by the M/V Berge Banker almost two weeks earlier (Lehr et al, 1997). A lack of current measurements off the Texas coast had severely limited the response community's ability to predict the landfall of the product.…”
Section: Introductionmentioning
confidence: 99%